Local radiotherapy in extensive-stage small-cell lung cancer sustainably boosts the clinical benefit of first-line immunotherapy: a case report - Wang, Hongming; Wang, Nuoni; Li, Shiyan; Du, Yangfeng; Wu, Tao; Tian, Wei; Dong, Wen; Liu, Xiaoyang; Zhang, Yan; Zheng, Jiang; Xiao, Zemin; Wu, Zhijun (Frontiers in Immunology, 2024)
Background: Extensive-stage small-cell lung cancer (ES-SCLC) has a dismal prognosis owing to its high aggressiveness, rapid drug resistance, and early metastasis. ES-SCLC responds well to first-line chemotherapy, and chemotherapy coupled with immunotherapy can further improve overall survival. However, the long-term survival of patients remains unsatisfactory because of its high recurrence rate and the poor efficacy of second-line treatment. Although local radiotherapy is an important component of the overall treatment for ES-SCLC, its value in the age of immunotherapy remains controversial. Case description: A 54-year-old male with ES-SCLC achieved a complete response (CR), as determined using enhanced computed tomography (CT) after four cycles of immunochemotherapy (serplulimab, carboplatin, and etoposide). Whole-body positron emission tomography-CT was performed during maintenance treatment with serplulimab, which showed primary lung, liver, and bone metastatic lesions with CR. However, several mediastinal lymph nodes exhibited glucose metabolism uptake, and new lesions appeared on the head. The patient underwent palliative radiotherapy of the head and consolidative thoracic radiotherapy of the chest and continued maintenance treatment with serplulimab. Subsequent magnetic resonance imaging of the head suggested good control of metastatic lesions (CR). The patient received first-line immunotherapy for approximately 20 months. Conclusions: This report presents a patient with ES-SCLC who underwent local radiotherapy in addition to serplulimab as maintenance therapy. Although the programmed death-ligand 1 (PD-L1) expression level was negative and a PD-1 inhibitor instead of a PD-L1 inhibitor was used, the patient did not experience significant pneumonia during treatment, and the efficacy of the current treatment was evident. This treatment model warrants further clinical investigation.